The thioredoxin homolog YbbN functions as a chaperone rather than as an oxidoreductase - Kthiri, Fatoum (2008)
Escherichia coli contains two thioredoxins, Trx1 and Trx2, and a thioredoxin-like protein, YbbN, which presents a strong homology in its N-terminal part with thioredoxins, and possesses a 20 kDa C-terminal part of unknown function. We reported previously that YbbN displays both protein oxido-reductase and chaperone properties in vitro. In this study, we show that an ybbN-deficient strain displays an increased sensitivity to thermal stress but not to oxidative stress, a normal redox state of its cellular proteins but a decreased expression of several cytoplasmic proteins, including EF-Tu, DnaK, GroEL, trigger factor and several Krebs cycle enzymes, suggesting that the chaperone properties of YbbN are more important in vivo than its redox properties. YbbN specifically interacts with DnaK and GroEL, as shown by reverse purification. It increases 4-fold the rate of protein renaturation in vitro by the DnaK chaperone machine, suggesting that it cooperates with DnaK for the optimal expression of several cytoplasmic proteins.